E-Module Based on Local Wisdom Ngubat Padi Improves Students' Social Care Character - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Juwita Saputri (Universitas Pendidikan Ganesha, 2021)
The use of teaching materials is essential for a teacher to deliver learning materials. Moreover, the selection of the wrong teaching materials can affect the character of students who will become weak. This study aims to analyze the relationship between social care characters integrated with electronic modules based on local wisdom of rice cultivation. The research method uses associative quantitative research, which aims to link an indicator. The research subjects were fourth-grade students, with the sampling technique being total sampling. The data collection instrument used was a questionnaire. Data analysis used descriptive statistics by using a correlation test to determine the relationship between two variables. The results in this study are that the social character of the students has a suitable category, seen from the indicators of social care character after using an electronic module based on local wisdom, strengthened by the correlation results obtained by 0.969 and produces a positive relationship. Therefore, teachers need to implement electronic modules based on local knowledge in learning to instill social care characters in students.